The state and upland populations: Ivory, Cattle and Guns in Nomansland 1820-1880 - Arkert, Ross (Department of Historical Studies, 2025)
This thesis examines trade and illicit networks in the area of the southern Drakensberg known as Nomansland through the commodities of ivory, cattle and guns in the period 1820 to 1880. In doing so it proposes that the ivory economy pursued by Botwas in the 1820s and 1830s constituted a resistance or escape economy meaning that it allowed them to evade state appropriation and violence. It also examines discourse about the area and argues that the area was described as disordered, lawless, unsettled and in a state of war. Further it argues that these descriptions were closely tied to cattle raiding in the area and that they served as justification for the imposition of colonial order through a series of treaty negotiations in the 1840s and 1850s which granted control of the area to Faku in 1844, ceded the area from him in 1850 and allowed the settlement of the Griqua in the area in 1862. Lastly it examines the symbiotic relationship between governance and resistance which emerged in the 1870s and 1880s. It argues that the commodity of guns was both a commodity of governance and a site of resistance. It examines how state structures began to be established in the area in the 1870s and 1880s but also how elements of a resistance economy continued to be present, for example, through smuggling networks. The thesis thus examines the relationship between state discourse around the economic activity in the area which described this activity as illicit and the economic activity of the inhabitants of the area which constituted a resistance or escape economy.